(untitled) (Journal of Nuclear Technology in Applied Science, 2025)
The present work describes raw banana peel (RBP) adsorption characteristics for chlorophenols from tap and river water samples. Also, aminated banana peel (AmBP) was prepared by the oxidative cleavage treatment of raw-BP from carbonyl groups, which were further reacted with ammonia to create new amine and imine groups in BP to give the resulting. FTIR, SEM, and XRD analyses described the derived adsorbents. Prepared AmBP was used for the removal of cobalt (II), the RBP was applied for removing 4-chloro-2-nitrophenol,4-chlorophenol, and 2,4,6-trichlorophenol from tap and river water before quantification with ICP OES for cobalt and HPLC-UV for chlorophenols. The absorption was maximal at pH 7.0 for cobalt (II), and pH 5.0 for chlorophenols. The shaking time was 30 minutes, and the adsorbent weight was 0.1 g. Desorption was affected by 0.1 mol/l HCl and 50% (v/v) methanol, respectively. Monolayer capacity adsorption by Langmuir isotherm was 8.5 mg/g for cobalt and from 6.5 to 10.5 mg/g for chlorophenols. Removal of the studied pollutants from tap water and river water was applied, and they showed capture ranging from 88.9-108.1 % for cobalt and from 80- 92% for chlorophenols.